Magnetically dependent photovoltages in permalloy films and gratings - Md Afzalur Rab; David W. Keene; Sean Nesbit; Terence Baker; Natalia Noginova (Scientific Reports)
Abstract Significant photoinduced voltages observed in permalloy structures consist of two contributions with different origins, which depend on illumination conditions, structure geometry and magnetic field in distinct ways. The first component is the plasmon drag effect voltage closely associated with plasmon propagation. The second contribution is magnetically dependent and can be related to photoinduced gradients in the sample temperature and spin polarization. Possible mechanisms of the effect are discussed.